Ingestion of a Pre-bedtime Protein Containing Beverage Prevents Overnight Induced Negative Whole Body Protein Balance in Healthy Middle-Aged Men: A Randomized Trial - Karagounis, Leonidas G.; Beaumont, Maurice; Donato-Capel, Laurence; Godin, Jean-Philippe; Kapp, Anne-France; Draganidis, Dimitrios; Pinaud, Stéphane; Vuichoud, Jacques; Shevlyakova, Maya; Rade-Kukic, Koraljka; Breuillé, Denis (Frontiers in Nutrition, 2019)
Age related muscle wasting leads to overall reductions of lean body mass, reduced muscle strength and muscle function resulting in compromised quality of life. Utilizing novel nutritional strategies to attenuate such losses is of great importance in elderly individuals. We aimed to test if a complete dietary supplement containing 25g of milk proteins and ingested in the evening before bed would improve protein metabolism in terms of whole body protein balance over a 10h overnight period following ingestion of the test drink in healthy middle-aged male subjects. In addition we also assessed the rates of muscle protein synthesis during the second half of the night in order to see if previously reported extended amino acidemia during sleep results in increased rates of muscle protein synthesis. Seventeen healthy middle-aged male subjects (59.4±3.2 yr) consumed a dietary supplement drink at 21:00 containing either 25g milk protein concentrate, 25g maltodextrin, 7.75g canola oil (treatment group) or an isocaloric protein void drink (placebo group). Muscle protein synthesis was assessed from a muscle biopsy following the continuous intravenous infusion of 13C- phenylalanine for 5 h (from 03:00 to 08:00). Whole body protein balance was greater in the treatment group (-0.13±11.30 g prot/10h) compared to placebo (-12.22±6.91 g prot/10h) (P≤0.01). In contrast, no changes were observed on rates of muscle protein synthesis during the second half of the night. Ingestion of a dietary supplement containing 25g of milk proteins significantly reduced the negative protein balance observed during the night. Therefore, pre-bedtime protein ingestion may attenuate overnight losses of lean tissue in healthy elderly men. Despite increases in aminoacidemia during the second part of the night, no changes were observed in the rates of muscle protein synthesis during this time.